Regulation of aromatic amino acid transport by tRNA: role of 2-methylthio-N6-(delta2-isopentenyl)-adenosine. - Buck, M (1981)
E. coli growing rapidly in media where ferric iron is not freely available contain a population of specifically undermodified tRNAs. These tRNAs contain isopentenyl adenosine instead of the usual methylthioisopentenyl adenosine adjacent to the 3' end of the anticodon. Iron restricted E. coli also show an enhanced capacity to transport aromatic amino acids into the cell. Our work shows that undermodified tRNAs for phe, tyr and trp can function as positive regulatory elements of the aromatic amino acid transport system in E. coli. This iron related metabolic control, mediated through a specific post-transcriptional modification of the tRNAs, may be an important mechanism for adapting E. coli for growth in an iron restricted environment.